2016
DOI: 10.1242/jcs.174235
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB-modulated microRNAs miR-195 and miR-497 inhibit myoblast proliferation by targeting Igf1r, Insr and cyclin genes

Abstract: MicroRNAs (miRNAs) play important roles in the development of skeletal muscle. In our previous study, expression of miR-195 and miR-497 were shown to be upregulated during muscle development in pigs. In this study, we investigated the roles of these two miRNAs in myogenesis and analyzed their transcriptional regulation. Our results showed that miR-195 and miR-497 were upregulated during muscle development and myoblast differentiation. Moreover, miR-195 and miR-497 inhibited proliferation but not differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 56 publications
5
51
0
1
Order By: Relevance
“…TNF-α induces synthesis of miRNAs, including miR-155-5p and miR-146b-5p (55), which are upregulated in BOO patients. In line with downstream activation of NFkB, we detected downregulation of abundant miR-497-5p, which has been described as inhibited by NFkB (56). It targets SMAD3 (57), JUN, FOSL1, TNFSF9, CCND1, and other mRNAs involved in pathways altered in BOO patients.…”
Section: Discussionsupporting
confidence: 57%
“…TNF-α induces synthesis of miRNAs, including miR-155-5p and miR-146b-5p (55), which are upregulated in BOO patients. In line with downstream activation of NFkB, we detected downregulation of abundant miR-497-5p, which has been described as inhibited by NFkB (56). It targets SMAD3 (57), JUN, FOSL1, TNFSF9, CCND1, and other mRNAs involved in pathways altered in BOO patients.…”
Section: Discussionsupporting
confidence: 57%
“…According to the flow cytometry results, despite the tiny difference between miR-696 mimics group and NC group, it could be of biological significance. The similar results to our study were also reported in several previous studies 17, 49. Besides, the genes involved in cell cycle regulation, such as cyclin D1, cyclin E and Cdk4, were down-regulated or up-regulated when miR-696 was over-expressed or inhibited (Figure 2F and K).…”
Section: Discussionsupporting
confidence: 92%
“…Wei et al observed that p65 (also known as Rel A, the active subunit of NF-κB) can directly bind to a specific miR-497 promoter site in C2C12 myoblast cells and reduce its expression, as determined by luciferase and ChIP-PCR assays [49]. However, Mechtler et al reported that PIPK-1 and IL-1β, which activate NF-κB, can increase the miR-497 level [50], though the direct relationship between miR-497 and NF-κB and the miR-497 gene NF-κB binding site was not exhaustively described.…”
Section: Regulation Mechanisms Of Mir-497 Expressionmentioning
confidence: 99%
“…Additionally, our lab demonstrated that suppressed IGF-1R protein expression via miR-497 up-regulation was able to re-sensitize pancreatic cancer cells to gemcitabine and that plasma IGF-1R can discriminate pancreatic cancer from other pancreatic tumors [64]. Furthermore, insulin receptor (IR), which mediates similar downstream signaling pathways as IGF-1R, has also been verified as an miR-497 target, and it plays an important role in myogenesis [49] and metabolic regulation [85]. Such studies indicate that miR-497-IGF-1R/IR is likely a clinically significant tumor suppressor-oncogene pair in human carcinomas and a critical mediator of normal biological functions.…”
Section: Direct Targets Of Mir-497mentioning
confidence: 99%
See 1 more Smart Citation